2020
DOI: 10.3390/ijms22010248
|View full text |Cite
|
Sign up to set email alerts
|

Promising Antioxidant Activity of Erythrina Genus: An Alternative Treatment for Inflammatory Pain?

Abstract: The negative impact that oxidative stress has on health is currently known. The complex mechanism of free radicals initiates a series of chain reactions that contribute to the evolution or development of different degenerative disorders. Likewise, these disorders are usually accompanied by inflammatory processes and, therefore, pain. In this sense, reactive oxygen species (ROS) have been shown to promote the nociceptive process, but effective treatment of pain and inflammation still represents a challenge. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…plant can scavenge free radicals and reduce the neurotoxicity in by 6-OHDA in SH-SY5Y cells. Furthermore, Jiménez-Cabrera et al [ 91 ] indicated that the Erythrina genus produces a wide range of secondary metabolites, including flavanones, isoflavones, isoflavones, and pterocarpans, namely sigmoidin A and B, erycristagallin, abyssinone V-4′-methyl ether, waragalone, mildbenone, 2″- O -galloyl orientin, neobavaisoflavone, and hypaphorine, which are responsible for the antioxidant activity of the plant. The beta-carboline alkaloids harmalol, harmaline, and harmine extracted from Peganum harmala can eliminate lipid and protein oxidation in the brain and also the death of dopaminergic neurons [ 92 ].…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%
“…plant can scavenge free radicals and reduce the neurotoxicity in by 6-OHDA in SH-SY5Y cells. Furthermore, Jiménez-Cabrera et al [ 91 ] indicated that the Erythrina genus produces a wide range of secondary metabolites, including flavanones, isoflavones, isoflavones, and pterocarpans, namely sigmoidin A and B, erycristagallin, abyssinone V-4′-methyl ether, waragalone, mildbenone, 2″- O -galloyl orientin, neobavaisoflavone, and hypaphorine, which are responsible for the antioxidant activity of the plant. The beta-carboline alkaloids harmalol, harmaline, and harmine extracted from Peganum harmala can eliminate lipid and protein oxidation in the brain and also the death of dopaminergic neurons [ 92 ].…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%
“…For this reason, attention has been drawn towards the use of naturally occurring antioxidant in plants containing high bioactive flavonoids, which have a strong potential to scavenge free radicals. Species of Erythrina are found to have high antioxidant properties (3) . Our study also showed that E. stricta is potentially a good source of such beneficial antioxidant compounds.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Certain species contains compounds that are potent central nervous system depressants, hypotensive, neuromuscular blockers, and sedatives. Their secondary metabolites such as flavonoids and pterocarpans were shown to have anti-inflammatory property (2,3) . Alkaloids from some species were demonstrated to have anticonvulsant, anxiolytic, curare-like activity, insecticidal and cytotoxic activities (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous in silico approach disclosed that the radical scavenging activity of Erythrina's flavanone, namely, mildbone and mildbenone, is predominantly associated with the second bond dissociation enthalpy of a second hydrogen atom transfer (Anouar, 2016). Mildbone and mildbenone, polar metabolites in Erythrina, were suggested to contribute to the various biological activities of Erythrina plants (Jiménez-Cabrera et al, 2020).…”
Section: Radical Scavenging Activity Of the Phytochemicalsmentioning
confidence: 99%